The causal-effect of bed rest and post-dural puncture headache in patients receiving diagnostic lumbar puncture: A prospective cohort study. Issue 8 (1st June 2021) - Tai, Chien-Shu; Wu, Shang-Liang; Lin, Shao-Yu; Liang, Ying; Wang, Shuu-Jiun; Chen, Shih-Pin
Abstract : Background: Post-dural puncture headache (PDPH) is the most common complication of lumbar puncture. Patients who received lumbar puncture were previously suggested to remain in bed for a certain time to prevent PDPH; however, this concept was challenged by recent studies. We aimed to investigate whether ambulation instead of resting supine following lumbar puncture could increase the risk of PDPH. Methods: The study used a prospective cohort design, applying convenience sampling among patients who received diagnostic lumbar puncture between January and September 2018 in the neurology ward of a tertiary medical center. The patients who fulfilled the inclusion criteria were informed that the current practice suggests lying supine for 6 to 8 hours after lumbar puncture, but they were allowed to either follow the suggestion or ambulate by their wills. The timing of bed rest was recorded, in addition to other possible risk factors of PDPH. The study endpoint is the presence or absence of PDPH within 48 hours of lumbar puncture. Results: A total of 137 patients who received lumbar puncture were enrolled, including 103 with bed rest following lumbar puncture and 34 without. There was no difference in demographics between the two groups. PDPH was found in 21 patients, with a total follow-up period of 5959 person-hours and an incidence density of 0.35%. There was no significant difference between the incidence of PDPH between the two groups (non-bed rest group 5.9% vs bed rest group 18.4%; p = 0.078), nor was incidence density (non-bed rest group 0.13% vs bed rest group 0.43%, p = 0.113). The results remained the same after adjusting for age. Conclusion: Bed rest following lumbar puncture does not prevent PDPH, and even leads to a marginally increased risk of PDPH. Amendment to the current practice guideline post-lumbar puncture care might be needed to improve patient care.